Pengaruh Pengenalan Huruf Abjad Melalui Kartu Huruf Terhadap Kemampuan Kognitif Anak Usia 4-5 Tahun Di Tk Tarbiyatul Islamiyah - Silvia Nurul Afifah; Atik Rosowati; Rufaidah Laila; Fitri Nihayatun Nadziroh; Hum Amanatin (Institut Agama Islam Negeri Metro, 2023)
Early childhood is a child with an age range of 0-8 years. At this time the child begins to develop rapidly which is called the golden age, which is the period when the child's brain development reaches 80%. This development includes six aspects, namely physical-motor, social-emotional, art, language, religious morals, and cognitive. This standard is the reference used by the NAEYC (National Association for Education for Young Children). At this stage the child experiences a sensitive period, the child gets a stimulus or stimulus from outside themselves. The media used in this research is letter cards. Based on the reality in Tarbiyatul Islamiyyah Kindergarten, namely the lack of ability to recognize letters. From the data in the assessment of the development of the language aspect and based on the results of observations on 18 children it is known that 25% of them meet the good criteria. And 50% of children meet the sufficient criteria, and 25% have fewer criteria. In this study, researchers used quantitative methods. With the results of independent descriptive values, namely the highest mean value is 3.93, and the lowest mean value is 2.66. The highest standard deviation is 0.84 and the lowest standard deviation is 0.25. And the results of the dependent descriptive value are the highest mean value is 3.7 and the lowest mean value is 2.9. The highest standard deviation value is 0.7 and the lowest standard deviation value is 0.5. With the final count, results show results that get a significant influence.